Social Investment Management of PT. Chevron Pacific Indonesia in the framework of National Defense - Legionosuko, Tri; Halkis, Mhd (Technium Social Sciences Journal, 2021)
Ethics in a multinational company environment is related to business problems, but the position of corporate partnership determines sustainable companies. The study aims to integrate the concept of social investment (SI) with state defense in multinational mining companies’ environment. Social Investment (SI) business ethics as part of Corporate Citizenship (CC) has a different concept base. CSR for companies is an honest effort for companies towards the surrounding community. Whereas the State Defense is a political concept of the State that regulates citizens’ rights and obligations in defending the country. The ethnographic method can combine the CSR and State Defense models in the multinational company oil mine environment. Chevron Pacific Indonesia Inc.’s CSR in international companies is called Social Investment (SI) has a dilemma; because CSR is seen as a long-term corporate interest, on the other hand, the regional Government distributes a small portion of profits to the surrounding community. After analyzing PT Chevron Pacific Indonesia’s CSR and the Regional Government’s strategy in realizing public welfare in the context of state defense, researchers can formulate the Corporate Citizenship (CC) as the State Defense CSR model.